precal

rewrite cosx/secx-1 not in fractional form

  1. 👍 0
  2. 👎 0
  3. 👁 99
asked by joe
  1. If you mean (cosx/secx) -1 , that equals cos^2 -1, which equals -sin^2 x.

    Do you instead mean cosx/(secx -1) ?

    1. 👍 0
    2. 👎 0
    posted by drwls
  2. yes i meant to have it with parantheses

    1. 👍 0
    2. 👎 0
    posted by joe

Respond to this Question

First Name

Your Response

Similar Questions

  1. urgent precal

    What is cosx/ (secx-1) not in fractional form?

    asked by joe on January 10, 2010
  2. desperate for help in precal

    how do you write (cosx)/(secx-1) without being in fractional form?

    asked by george on January 10, 2010
  3. Pre-Calc

    Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 -

    asked by Dave on January 2, 2007
  4. Calculus 2 Trigonometric Substitution

    I'm working this problem: ∫ [1-tan^2 (x)] / [sec^2 (x)] dx ∫(1/secx)-[(sin^2x/cos^2x)/(1/cosx) ∫cosx-sinx(sinx/cosx) ∫cosx-∫sin^2(x)/cosx sinx-∫(1-cos^2(x))/cosx sinx-∫(1/cosx)-cosx sinx-∫secx-∫cosx

    asked by Janice on March 15, 2015
  5. precal

    1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a

    asked by olivia on March 25, 2012
  6. math

    1. (sinx/cscx)+(cosx/secx)=1 2. (1/sinxcosx)-(cosx/sinx)=tanx 3. (1/1+cos s)=csc^2 s-csc s cot s 4. (secx/secx-tanx)=sec^2x+secxtanx 5. (cosx/secx-1)-(cosx/tan^2x)=cot^2x

    asked by Tom on April 10, 2008
  7. Pre Calculus

    Having trouble verifying this identity... cscxtanx + secx= 2cosx This is what I've been trying (1/sinx)(sinx/cosx) + secx = 2cosx (1/cosx)+(1/cosx) = 2 cosx 2 secx = 2cosx that's what i ended up with, but i know it's now right.

    asked by Alex on April 11, 2013
  8. Simplifying with Trigonometry Identities

    Hi, I am a senior in High School having a really difficult time with two problems. I have to prove using the trigonometric identities that they equal each other but I am having a really hard time trying to get them to equal each

    asked by amanda on March 7, 2007
  9. Pre-Calculus

    How do you verify: 1.) sinxcosx+sinx^3secx=tanx 2.) (secx+tanx)/(secx-tan)=(secx+tanx)^2 I tried starting from the left on both problems, but am stuck. like I said before, change everything into sines and cosines. for the first

    asked by Corin on May 4, 2007
  10. Precalculus/Trig

    I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't

    asked by Heather on August 15, 2014

More Similar Questions